Biodegradable resin composition and biodegradable resin molded product

JP2025025436APending Publication Date: 2025-02-21TOPPAN HOLDINGS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023130185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

Smart Images

  • Figure 2025025436000001
    Figure 2025025436000001
Patent Text Reader

Abstract

To provide a biodegradable resin composition and biodegradable resin molded product in which a decomposition rate of biodegradable resin can be accelerated.SOLUTION: A biodegradable resin composition contains biodegradable resin and titanium oxide particles. When the crystal structure of titanium oxide particles is an anatase type, the particle diameter of titanium oxide particles is 5nm or more and 20nm or less, and the content of titanium oxide particles is 2 mass% or more and 5 mass% or less, when the crystal structure of titanium oxide particles is a rutile type, the particle diameter of titanium oxide particles is 5nm or more and 20nm or less, and the content of titanium oxide particles is 0.5 mass% or more and 5 mass% or less, and a biodegradable resin molded product is formed of the biodegradable resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biodegradable resin composition and a biodegradable resin molded article. [Background technology]

[0002] In recent years, biodegradable resins have begun to be used for packages and materials because there is a risk that packages and materials made of resin materials may cause environmental pollution when they are discarded, etc. To enable use as packages and materials, such biodegradable resins have been made to have a decomposition rate adjusted by additives so that they can be decomposed by microorganisms after disposal while still retaining the mechanical strength required for molded products (see, for example, Patent Document 1 below, etc.). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-323177 A [Patent Document 2] Japanese Patent Application Publication No. 8-001806 [Patent Document 3] JP 2002-195951 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the decomposition speed of conventional biodegradable resins as described above was not sufficient depending on the application. For example, when biodegradable resins are applied to containers used for food such as lunch boxes, or to agricultural, horticultural, or construction films and sheets used as outdoor covers, food and soil stains adhere to the resins. Therefore, they are difficult to reuse or recycle, and must be disposed of as waste, and there is a demand for faster decomposition speed after disposal.

[0005] In view of the above, an object of the present invention is to provide a biodegradable resin composition and a biodegradable resin molded article that can accelerate the decomposition rate of a biodegradable resin. [Means for solving the problem]

[0006] In order to solve the above-mentioned problems, the biodegradable resin composition according to the first invention contains a biodegradable resin and titanium oxide particles, the titanium oxide particles have an anatase crystal structure, the titanium oxide particles have a particle diameter of 5 nm or more and 20 nm or less, and the content of the titanium oxide particles is 2 mass% or more and 5 mass% or less.

[0007] Furthermore, in order to solve the above-mentioned problems, the biodegradable resin composition according to the second invention contains a biodegradable resin and titanium oxide particles, and is characterized in that the crystal structure of the titanium oxide particles is rutile type, the particle diameter of the titanium oxide particles is 5 nm or more and 20 nm or less, and the content of the titanium oxide particles is 0.5 mass % or more and 5 mass % or less.

[0008] In the biodegradable resin composition according to the first invention, the titanium oxide particles preferably have a particle diameter of 5.5 nm or more and 6.4 nm or less.

[0009] In addition, in the biodegradable resin composition according to the first invention, the content of the titanium oxide particles is preferably 2.5% by mass or more and 3.4% by mass or less.

[0010] In the biodegradable resin composition according to the second invention, the particle diameter of the titanium oxide particles is preferably 9.5 nm or more and 10.4 nm or less.

[0011] In the biodegradable resin composition according to the second invention, the content of the titanium oxide particles is preferably 0.5% by mass or more and 3.4% by mass or less.

[0012] In the biodegradable resin composition according to the first or second invention, the biodegradable resin is preferably polylactic acid (PLA).

[0013] On the other hand, in order to solve the above-mentioned problems, the present invention provides a biodegradable resin molded article which is molded from the above-mentioned biodegradable resin composition.

[0014] The biodegradable resin shaped article according to the present invention is preferably in the form of a sheet or film in the above-mentioned biodegradable resin shaped article according to the present invention. Effect of the Invention

[0015] According to the biodegradable resin composition and biodegradable resin molded body of the present invention, when irradiated with light, radicals are generated by the titanium oxide particles, which deteriorate and decompose the biodegradable resin, thereby promoting the biodegradation of the biodegradable resin and enabling the biodegradable resin to be rapidly decomposed, thereby accelerating the decomposition rate of the biodegradable resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The embodiments of the biodegradable resin composition and the biodegradable resin molded article according to the present invention are described below. Note that the present invention is not limited to the embodiments described below, and various technical matters described in each embodiment can be appropriately combined or replaced as necessary.

[0017] [First embodiment] A first embodiment of the biodegradable resin composition and the biodegradable resin molded article according to the present invention will be described.

[0018] <Biodegradable resin composition> The biodegradable resin composition according to this embodiment contains a biodegradable resin and titanium oxide particles, the titanium oxide particles have an anatase crystal structure, a particle diameter of 5 nm or more and 20 nm or less, a titanium oxide particle content of 2 mass % or more and 5 mass % or less, and is in the form of pellets, compounds, etc.

[0019] 《Biodegradable resin》 Biodegradable resins have ester bonds, and are broken down into smaller molecules by hydrolysis. Specific examples of biodegradable resins include polylactic acid (PLA), polybutylene succinate (PBS), and polybutylene adipate terephthalate (PBAT), with PLA being particularly preferred.

[0020] Titanium oxide particles Titanium oxide particles have the function of promoting the decomposition of biodegradable resins, and when irradiated with light, they can generate oxygen radicals from oxygen molecules in the atmosphere or hydroxyl radicals from water molecules, thereby degrading and decomposing the biodegradable resin. Such decomposition of biodegradable resins by photodegradation proceeds more quickly than biodegradation. Therefore, biodegradable resins are first decomposed by photodegradation, becoming smaller molecules and increasing their surface area, which promotes biodegradation and allows them to be decomposed quickly.

[0021] The titanium oxide particles have a particle diameter of 5 nm to 20 nm (preferably 5.5 nm to 6.4 nm, more preferably 6 nm). If the particle diameter is less than 5 nm, the area in which the titanium oxide exists in the resin becomes too small, and decomposition due to photodegradation cannot be sufficiently caused. If the particle diameter is more than 20 nm, the surface area becomes too small, and decomposition due to photodegradation cannot be sufficiently caused.

[0022] The titanium oxide particles are contained in the composition in an amount of 2% by mass or more and 5% by mass or less (preferably 2.5% by mass or more and 3.4% by mass or less, more preferably 3% by mass). If the amount is less than 2% by mass, the amount of titanium oxide present in the resin becomes too small, and decomposition due to photodegradation cannot be sufficiently caused. If the amount is more than 5% by mass, the surface area becomes too small, and decomposition due to photodegradation cannot be sufficiently caused.

[0023] <Biodegradable resin molded body> The biodegradable resin molded article according to this embodiment is molded from the above-mentioned biodegradable resin composition, and examples of such molded articles include containers used for lunch boxes for storing food, and films and sheets for agricultural, horticultural, and construction use as outdoor covers and other materials.

[0024] Such a biodegradable resin molded article is molded into a desired shape and thickness by a general, conventionally known means. For example, a container can be manufactured by injection molding, blow molding, vacuum molding, etc. A film can be manufactured by inflation molding, etc. A sheet can be manufactured by extrusion molding, etc. In addition, it is also possible to integrally provide a film or sheet of another material so as to cover it, for example, by a die coater, etc.

[0025] In the biodegradable resin composition and the biodegradable resin molded article according to the present embodiment, when light is irradiated, as described above, radicals are generated by the titanium oxide particles, which deteriorate and decompose the biodegradable resin, and therefore the biodegradation of the biodegradable resin is promoted and the biodegradation is rapidly performed.

[0026] Therefore, according to the biodegradable resin composition and biodegradable resin molded body of this embodiment, the decomposition rate of the biodegradable resin can be increased, and therefore the composition and the biodegradable resin molded body can be suitably used for containers used for storing food such as lunch boxes and which are subject to food stains, and for agricultural, horticultural and construction films and sheets used as outdoor covers and other materials and which are subject to soil stains.

[0027] [Second embodiment] A second embodiment of the biodegradable resin composition and the biodegradable resin molded article according to the present invention will be described below, however, the description of the same parts as those in the above-mentioned embodiment will be omitted.

[0028] <Biodegradable resin composition> The biodegradable resin composition according to this embodiment contains a biodegradable resin and titanium oxide particles, the titanium oxide particles having a rutile crystal structure, a particle diameter of 5 nm or more and 20 nm or less, a titanium oxide particle content of 0.5% by mass or more and 5% by mass or less, and is in the form of pellets, compounds, or the like.

[0029] Titanium oxide particles The titanium oxide particles have a particle diameter of 5 nm to 20 nm (preferably 9.5 nm to 10.4 nm, more preferably 10 nm). If the particle diameter is less than 5 nm, the area in which the titanium oxide exists in the resin becomes too small, and decomposition due to photodegradation cannot be sufficiently caused. If the particle diameter is more than 20 nm, the surface area becomes too small, and decomposition due to photodegradation cannot be sufficiently caused.

[0030] The titanium oxide particles are contained in the composition in an amount of 0.5% by mass to 5% by mass (preferably 0.5% by mass to 3.4% by mass, more preferably 0.5% by mass to 3% by mass). If the amount is less than 0.5% by mass, the amount of titanium oxide present in the resin is too small, and decomposition due to photodegradation cannot be sufficiently caused. If the amount is more than 5% by mass, the surface area is too small, and decomposition due to photodegradation cannot be sufficiently caused.

[0031] <Biodegradable resin molded body> The biodegradable resin molded article according to this embodiment is molded from the above-mentioned biodegradable resin composition, as in the previously described embodiment, and examples of such molded articles include containers used for lunch boxes for storing food, and agricultural, horticultural, and construction films and sheets used as outdoor covers and other materials.

[0032] In the biodegradable resin composition and biodegradable resin molded article according to this embodiment, as in the case of the above-mentioned embodiment, when light is irradiated, the titanium oxide particles generate radicals that deteriorate and decompose the biodegradable resin, thereby accelerating the biodegradation of the biodegradable resin and causing it to decompose rapidly.

[0033] Therefore, according to the biodegradable resin composition and biodegradable resin molded body of this embodiment, as in the case of the above-mentioned embodiment, the decomposition rate of the biodegradable resin can be increased, and therefore the composition and the biodegradable resin can be suitably used for containers used for food storage such as lunch boxes and which are subject to food stains, and agricultural, horticultural, and construction films and sheets used as outdoor covers and other materials and which are subject to soil stains. EXAMPLES

[0034] Examples of the biodegradable resin composition and the biodegradable resin molded article according to the present invention will be specifically described below. Note that the present invention is not limited to only the specific examples described below.

[0035] [Preparation of test specimens and comparison specimens] Test specimen 1 Anatase-type titanium oxide particles with a particle diameter of 6 nm were mixed (3 mass% of the total) with polylactic acid (PLA), a biodegradable resin, to obtain a biodegradable resin composition for specimen 1. This was then extruded into a sheet shape with a thickness of 0.2 mm using an extrusion molding machine to produce specimen 1, a sheet of biodegradable resin molding.

[0036] Test specimen 2 Specimen 2, a sheet that is a biodegradable resin molded article, was prepared in the same manner as Specimen 1, except that the blending amount of titanium oxide particles was set to 2 mass % based on the total.

[0037] Test specimen 3 Specimen 3, a sheet that was a biodegradable resin molded article, was prepared in the same manner as Specimen 1, except that the blending amount of titanium oxide particles was set to 5 mass % based on the total.

[0038] Test specimen 4 Specimen 4, which was a sheet of a biodegradable resin molded article, was prepared in the same manner as Specimen 1, except that the particle diameter of the titanium oxide particles was set to 5 nm.

[0039] Test specimen 5 Specimen 5, which was a sheet that was a biodegradable resin molded article, was prepared in the same manner as Specimen 1, except that the particle diameter of the titanium oxide particles was set to 20 nm.

[0040] Test specimen 6 Specimen 6, which was a sheet of a biodegradable resin molded article, was prepared in the same manner as Specimen 1, except that rutile-type titanium oxide particles having a particle diameter of 10 nm were used.

[0041] Test specimen 7 Specimen 7, a sheet that is a biodegradable resin molded article, was prepared in the same manner as Specimen 6, except that the blending amount of titanium oxide particles was 0.5 mass % based on the total.

[0042] Test specimen 8 Specimen 8, a sheet that was a biodegradable resin molded article, was prepared in the same manner as Specimen 6, except that the blending amount of titanium oxide particles was set to 5 mass % based on the total.

[0043] Test specimen 9 Specimen 9, a sheet that is a biodegradable resin molded article, was prepared in the same manner as Specimen 6, except that the particle diameter of the titanium oxide particles was set to 5 nm.

[0044] Test piece 10 Specimen 10, which was a sheet of a biodegradable resin molded article, was prepared in the same manner as Specimen 6, except that the particle diameter of the titanium oxide particles was set to 20 nm.

[0045] Comparison body 1 Comparative sample 1, which was a sheet made of a biodegradable resin molded article, was prepared in the same manner as test sample 1, except that the amount of titanium oxide particles was 1.5 mass % based on the total amount.

[0046] Comparison body 2 Comparative sample 2, which was a sheet of a biodegradable resin molded article, was prepared in the same manner as sample 1, except that the amount of titanium oxide particles was 6 mass % based on the total amount.

[0047] Comparison 3 Comparative sample 1, which was a sheet made of a biodegradable resin molded article, was prepared in the same manner as test sample 1, except that the particle diameter of the titanium oxide particles was set to 30 nm.

[0048] <Comparative example 4> Comparative sample 4, which was a sheet made of a biodegradable resin molded article, was prepared in the same manner as sample 6, except that the amount of titanium oxide particles was 0.3 mass % based on the total amount.

[0049] Comparison body 5 Comparative sample 5, which was a sheet of a biodegradable resin molded article, was prepared in the same manner as sample 6, except that the amount of titanium oxide particles was 6 mass % based on the total amount.

[0050] Comparison 6 Comparative sample 6, which was a sheet of a biodegradable resin molded article, was prepared in the same manner as sample 1, except that the particle diameter of the titanium oxide particles was 35 nm.

[0051] [Test Method] Tensile Test Five sample pieces (100 mm x 15 mm) were cut from each of the test pieces 1 to 10 and the comparison pieces 1 to 6 before and after the accelerated weathering treatment under the conditions below (a total of 10 pieces before and after the accelerated weathering treatment). Both ends of these sample pieces were pulled until they broke under the conditions below, and the breaking tensile strength against the thickness was measured. The average value was calculated before and after the accelerated weathering treatment, and the rate of change Rd (%) was calculated based on the following formula (1). If the rate of change Rd is -20% or less, it can be said that accelerated decomposition due to photodegradation has occurred sufficiently. The results are shown in Table 1 below.

[0052] Accelerated weathering treatment conditions Light source: Metal halide lamp ·Wavelength: 295~450nm ·Illuminance: 1.5kW / m 2 Irradiation time: 8 hours ·Temperature: 60℃ ·Humidity: 50%RH Water spray: 18 minutes every 2 hours

[0053] Tensile test conditions Tensile testing machine: Shimadzu Corporation "AG-X (product number)" Load cell: 10kN ·Temperature: 23℃ ·Humidity: 50%RH Grip distance (chuck distance): 50mm Pulling speed: 500mm / min

[0054] Rd = {(Fa-Fb) / Fb} × 100 (1) where Fa is the breaking tensile strength (N / mm) after accelerated weathering treatment relative to thickness, and Fb is the breaking tensile strength (N / mm) before accelerated weathering treatment relative to thickness.

[0055] <Chemiluminescence measurement test> Chemiluminescence measurement is a method for measuring the luminescence intensity of chemiluminescence generated when a sample is heated, and is a method for measuring the degree of oxidation of a sample. Chemiluminescence measurement is specified in the Japanese Industrial Standards (JIS) "K7351", and can be measured by a method using a known chemiluminescence analyzer. For example, it can be measured using the device shown in FIG. 1 of Patent Document 3.

[0056] In this measurement test, first, two circular sample pieces (18 mm in diameter) were cut out from each of the test pieces 1 to 10 and the comparative pieces 1 to 6 before and after the accelerated weathering treatment under the above conditions (a total of four pieces before and after the accelerated weathering treatment). Then, in accordance with JIS "K7351", a temperature rise measurement test under the following conditions was performed before and after the accelerated weathering treatment, and the maximum light emission amount CLub before the accelerated weathering treatment and the maximum light emission amount CLua after the accelerated weathering treatment were measured, and the ratio Ru (=CLua / CLub) was obtained. In addition, an isothermal measurement test under the following conditions was performed before and after the accelerated weathering treatment, and the maximum light emission amount CLcb before the accelerated weathering treatment and the maximum light emission amount CLca after the accelerated weathering treatment were measured, and the ratio Rc (=CLca / CLcb) was obtained. The results are shown in Table 1 below.

[0057] <Temperature rise measurement test conditions> Measurement device: Chemiluminescence analyzer "CLA-FS4 (product number)" manufactured by Tohoku Electronics Industry Co., Ltd. Atmosphere: Nitrogen gas ·Initial temperature: 50℃ Heating rate: 20℃ / min ·Final temperature: 220℃ Final temperature hold time: 10 minutes

[0058] Isothermal measurement test conditions Measurement equipment: Same as for temperature rise measurement test Atmosphere: Nitrogen gas ·Temperature: 100℃ Holding time: 5 minutes

[0059] [Test Results] The results of the tensile test and the chemiluminescence (CL) measurement test are shown in Table 1 below.

[0060] [Table 1]

[0061] As can be seen from Table 1, in the comparative samples 1 to 6, the change rate Rd was greater than -20%, and accelerated decomposition due to photodegradation did not occur sufficiently. In contrast, in the test samples 1 to 10, the change rate Rd was -20% or less, and accelerated decomposition due to photodegradation occurred sufficiently. From the above, it was confirmed that the present invention can promote the biodegradation of biodegradable resins and rapidly decompose them. [Industrial Applicability]

[0062] The biodegradable resin composition and biodegradable resin molded article according to the present invention can increase the decomposition rate of biodegradable resins and can therefore be used extremely beneficially in various industries.

Claims

1. Contains a biodegradable resin and titanium oxide particles, The titanium oxide particles have an anatase crystal structure, The particle diameter of the titanium oxide particles is 5 nm or more and 20 nm or less, The content of the titanium oxide particles is 2% by mass or more and 5% by mass or less. A biodegradable resin composition comprising:

2. Contains a biodegradable resin and titanium oxide particles, The titanium oxide particles have a rutile crystal structure, The particle diameter of the titanium oxide particles is 5 nm or more and 20 nm or less, The content of the titanium oxide particles is 0.5% by mass or more and 5% by mass or less. A biodegradable resin composition comprising:

3. The particle diameter of the titanium oxide particles is 5.5 nm or more and 6.4 nm or less. The biodegradable resin composition according to claim 1 .

4. The content of the titanium oxide particles is 2.5% by mass or more and 3.4% by mass or less. The biodegradable resin composition according to claim 1 .

5. The particle diameter of the titanium oxide particles is 9.5 nm or more and 10.4 nm or less. The biodegradable resin composition according to claim 2 .

6. The content of the titanium oxide particles is 0.5% by mass or more and 3.4% by mass or less. The biodegradable resin composition according to claim 2 .

7. The biodegradable resin is polylactic acid (PLA).

3. The biodegradable resin composition according to claim 1 or 2.

8. A product molded from the biodegradable resin composition according to claim 1 or 2. A biodegradable resin molded article comprising:

9. It is in the form of a sheet or film.

9. The biodegradable resin molded article according to claim 8.

Citation Information

Patent Citations

  • Molded form of photodegradable and biodegradable polymer

    JP1996001806A

  • Biodegradable resin composition with controlled biodegradation rate and method of its manufacturing

    JP2001323177A

  • Degradation judging method for sample and device used for it

    JP2002195951A